Implementasi Early Warnings System (EWS) dalam Menekan Tingkat Non Performing Financing (NPF) di Perbankan Syariah - Febriyanti, Novi (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2020)
The health of a bank based on sharia principles is in the interest of all parties involved, including the owner, bank management, public users of bank services, Bank Indonesia as the bank supervisory authority and other parties. The following article aims to discuss the principles of Sharia prudential banking through an early warning system (EWS) that Islamic banks usually apply. The research method used is qualitative with a field research approach and literature study with data collection techniques through observation, interviews and documentation. The results show that the application of an early warning measurement system for Islamic banks can be calculated using several indicators, namely including return on equity (ROE), return on assets (ROA), financing to deposit ratio (FDR), non-performing finance (NPF) and ratios. operating costs and operating income (BOPO). This is implemented to reduce the level of problematic financing caused by two factors, namely internal factors (the banking sector), namely the lack of maintenance that has been determined, accuracy in business analysis, understanding of the necessary needs, inclusion of sound policy requirements and pursuing targets. External factors (debtors) are natural disasters, decreased business, collateral, increased competition for business types, low education levels and family factors.